Preferences and expectations of end-users from a mental health educational portal: A qualitative study - Sara Pourrazavi; Somayeh Azimi; Ali Fakhari; Habibeh Barzegar; Mostafa Farahbakhsh (Tabriz University of Medical Sciences, 2024)
Background: Digital technologies play an essential role in health systems by providing new solutions to reduce the burden of mental illnesses and disorders. However, in many cases, user preferences and expectations are not considered in the design of portals. This study aims to explore the preferences and expectations of end-users from the features and capabilities of mental health educational portals. Methods: This qualitative study was conducted from January 2022 to January 2023 using the conventional content analysis approach. The participants were 20 individuals, selected through purposive sampling, ranging in age from 18 to 61, all of whom had prior experience using an educational portal. Data were collected via individual semi-structured interviews. Qualitative analysis was performed using MAXQDA 10 software. Results: After analyzing the data, the preferences and expectations of end-users were categorized into five main themes: to be reliable, mutual interaction capability, to be accessible, creating a stylish and attractive design, and attention to the quality and structure of the content. Conclusion: Considering the expectations and needs of users will enhance their acceptance and satisfaction with the portals. From the end-users' perspectives, the content, appearance, and structural or technical features a mental health educational portal are crucial for its effectiveness.